Epidemiologia molecular e estudo da diversidade genética da tuberculose no Estado de São Paulo - Moraes, Eloise Brasil de [UNESP] (2016)
Tuberculosis (TB) is a major cause of mortality, and Mycobacterium tuberculosis (M. tuberculosis), the causative agent. The study of molecular epidemiology associated with classical epidemiology, provides an understanding of the spread of M. tuberculosis and ads in epidemiological investigation, determining outbreaks and risk factors for transmission in the population. This study aimed to provide a more accurate view of the molecular epidemiology and genetic diversity of M. tuberculosis by MIRU-VNTR technique and get a better understanding of the relevance of the epidemiological and clinical potential of RDRio genotype in municipalities in the state of São Paulo, investigating possible associations with clinical and epidemiological data. Besides this study investigate possible transmission between contacts of patients with TB. Heterogeneity was observed in both regions that were grouped independently in phylogenetic analysis. Nevertheless some specific isolated from both regions showed high genetic similarity. When investigated epidemiological data of these patients 30% were from prisons. This suggests a recent transmission process within the penitentiaries to the general community between these two regions. Although the clustering rate found to be low, we noted in cluster formation the presence again of patients sharing the same genetic profile in different penitentiaries suggesting once more a transmission between distinct prision units. Regarding RDRio deletion was found high statistical significance for the factors and alcohol use by age group, with conflicting data already published in the literature. The results generated interesting questions that should be addressed in the future.